Analysis of Factors Affecting the Performance of Midwives on Family Planning Services in Paser Regency - Nurjannah, Nurjannah; Meutia, Meutia; Noviyanti, Mery (PT. Riset Press International, 2024)
Family planning programs have an important role in reducing maternal and child mortality, through preventing pregnancy, delaying gestational age and spacing pregnancies with the main target being couples of reproductive age. The health workers who are in charge of running the family planning program are midwives, the success of the family planning program is supported by the performance of midwives. Factors that affect the performance of midwives are workload, training, incentives, infrastructure and work motivation. Objective: To analyze the factors that influence the performance of midwives in Pasar District. Methods: Analytic survey research with a cross sectional study design. A sample of 88 people using Cluster proportional random sampling. The research instrument used a questionnaire. Data analysis was descriptive and statistical, namely multiple linear regression. Results: there is an effect of workload on the performance of midwives (p=0.025), there is an effect of training on the performance of midwives (p=0.000). there is an influence of incentives on the performance of midwives (p = 0.000), there is no effect of infrastructure on the performance of midwives (p = 0.217), there is an effect of work motivation on the performance of midwives (p = 0.000). Conclusion: There is an influence of workload, training, incentives, infrastructure and work motivation on the performance of midwives.